Pengaruh Katalis Cao/Fly Ash Dalam Produksi Biodiesel Dari Crude Palm Oil - Ramadhani, InayahTullah; Mustain Zamhari; Dilia Puspa (Jurnal Serambi Engineering, 2026)
This study aims to optimize biodiesel production from crude palm oil (CPO) by utilizing CaO/Fly Ash heterogeneous catalysts from limestone and coal combustion residues. Variations in the time and concentration of CaO/Fly Ash catalyst were tested to determine their effect on biodiesel yield percentage and product characteristics through esterification and transesterification processes. Limestone was used as the main source of CaO, while Fly Ash served to increase the stability, surface area, and support of the catalyst. The catalyst was analyzed using X-Ray Fluorescence (XRF) to determine the composition of the elements contained, while the effect of the catalyst on biodiesel was analyzed through density, viscosity, acid number, saponification number, and flash point tests. The transesterification process was carried out at 60, 90, and 120 minutes and with varying catalyst masses (8 g, 10 g, 12 g, 14 g) to obtain the optimum reaction conditions and the best characteristics for biodiesel. Optimal reaction conditions were achieved using 12 grams of CaO/Fly Ash catalyst and a reaction time of 120 minutes, resulting in the highest biodiesel yield of 86.6%, density of 863.9 kg/m3, viscosity of 4.35 cSt, a saponification number of 178.03 mg KOH/g, an acid number of 0.43 mg KOH/g, a cetane number of 54.7, and a flash point of 154oC with biodiesel characteristics that comply with the SNI 7182:2015 standard. This shows that the right combination of catalyst mass and reaction time can significantly increase biodiesel conversion efficiency. Excessive use of catalyst reduces efficiency due to the formation of side reactions.